Pengaruh Motivasi Dan Displin Kerja Terhadap Kinerja Karyawan Pada PT Volex Indonesia Di Kota Batam - Fitriani Harmita Mukhtar; Wasiman (Komunitas Dosen Indonesia, 2024)
This study aims to investigate the effect of work motivation and discipline on employee performance at PT Volex Indonesia in Batam City. High motivation can increase the performance level of employees by encouraging them to achieve company goals and make a greater contribution. Good work discipline also plays an important role in creating an efficient and orderly work environment, so that employees can work effectively and efficiently. This research uses a descriptive type with a quantitative approach and collects data through questionnaires distributed to 156 respondents of PT Volex Indonesia employees. Data analysis techniques using data quality tests, classic assumption tests, influence tests and hypothesis testing. The findings of multiple linear regression analysis show that motivation has an influence of 50.6% on employee performance at PT Volex Indonesia in Batam City, while work discipline has an influence of 31.3% on employee performance at PT Volex Indonesia in Batam City. The findings of the analysis of the coefficient of determination (R2) state that motivation and work discipline explain 70.7% of employee performance at PT Volex Indonesia in Batam City. The results of the partial and simultaneous analysis of the hypotheses show that work motivation and discipline have a significant positive effect on the performance of employees of PT Volex Indonesia in Batam City.